TRANSFORMING CHARACTER EDUCATION THROUGH DIGITAL TECHNOLOGY-BASED ISLAMIC RELIGIOUS EDUCATION: AN EMPIRICAL INVESTIGATION AND THE TAPAK MODEL - Nurfadilah Hasanah; Muhamad Ihsanuddin; Rini Oktaviani (Universitas Islam Depok, 2025)
The integration of digital technology into Islamic Religious Education (PAI) represents one of the most consequential pedagogical challenges facing Muslim educational institutions in the twenty-first century. This study empirically investigates the effectiveness of Google Classroom-mediated PAI instruction in transforming the character formation of students at Islamic secondary schools in Java, Indonesia. Grounded in Paulo Freire's critical pedagogy (1970) and Thomas Lickona's three-dimensional character framework (1991, 2004), the study employs a sequential explanatory mixed-methods design. Quantitative data were collected from 320 students across eight schools using the Character Formation Index (CFI), a 45-item validated instrument measuring religious character, digital integrity, and academic responsibility, before and after a 16-week implementation cycle. Qualitative depth was provided through semi-structured interviews with 48 students and 16 PAI teachers. Results revealed statistically significant and educationally substantial improvements across all three character dimensions: religious character increased by 38.6% (Cohen's d = 2.38), digital integrity by 45.4% (d = 2.01), and academic responsibility by 41.7% (d = 1.88). Crucially, pedagogical pattern—particularly the degree of dialogic-transformative use of the platform—emerged as a stronger predictor of character gain than school location or infrastructure quality. These findings ground the formulation of the TAPAK Model (Transformasi Aktif PAI berbasis Karakter / Active Character-Based PAI Transformation), a five-phase instructional framework that systematically operationalises Freirean praxis within Islamic pedagogical tradition. Implications for teacher professional development, curriculum reform, and equitable digital education policy are discussed.